Análise da aplicabilidade de indicadores de circularidade em uma empresa de reciclagem de resíduos de equipamentos eletroeletrônicos - Bertani, Izabela Ferro (2022)
Currently, the circular economy, which aims to add additional value to products through reuse and recycling, has been widely disseminated with the aim of reducing the extraction of virgin raw materials, among others. To measure advances towards a circular economy, several circularity indicators are used, as mentioned in the literature. Thus, this article aims to measure the circularity of two electricity meters. The conventional meter (A), produced with virgin polycarbonate (PC), and the smart meter (B), where 90% of the PC used comes from the Waste Electrical and Electronic Equipment (WEEE) recycling process. In the case studied, it comes from recycling the product at the end of its useful life (conventional meter (A)). Data collection was performed at SinctronicsTM (Center for Innovation in Sustainable Technology). To assess the circularity of the WEEE recycling process, the Material Circularity Indicator (MCI) proposed by the Ellen MacArthur Foundation was used, which aims to measure how circular the flow of a given product is. The results indicated a strong tendency to circularity when recycled raw material was added in the manufacture of the smart electric energy meter (product B), making it an attractive option to be used as a substitute for conventional meters.